1990
DOI: 10.3171/jns.1990.73.6.0871
|View full text |Cite
|
Sign up to set email alerts
|

Systems analysis of cerebrovascular pressure transmission: an observational study in head-injured patients

Abstract: In an observational study in head-injured patients, cerebrovascular pressure transmission was investigated using a systems analysis approach whereby the blood pressure (BP) waveform was used as a measure of an input stimulus to the cerebrovascular bed (CVB) and the intracranial pressure (ICP) waveform as the response to that stimulus. The transfer function is a measure of how much pressure is transmitted through the CVB at a given frequency and is calculated using Fourier analysis of the pressure waveforms. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
58
0
3

Year Published

1997
1997
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 21 publications
2
58
0
3
Order By: Relevance
“…2 There are two concepts regarding the origin of the lumbar cerebrospinal¯uid pulse wave (L-CSFPW): that it arises from pulsation of the spinal cord. 3,4 and that it is due to pulsation of the brain which is transmitted through the subarachnoid space of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…2 There are two concepts regarding the origin of the lumbar cerebrospinal¯uid pulse wave (L-CSFPW): that it arises from pulsation of the spinal cord. 3,4 and that it is due to pulsation of the brain which is transmitted through the subarachnoid space of the spine.…”
Section: Introductionmentioning
confidence: 99%
“…Slow waves of ABP, lasting from 20 seconds to 3 minutes, are almost always present in patients receiving mechanical ventilation and are of sufficient magnitude to provoke a vasomotor response. 1,20,23,24,27 Taking advantage of this fact, cerebrovascular pressure reactivity can be determined continuously without manipulation of ABP by monitoring the response of ICP to such changes in mean ABP.…”
mentioning
confidence: 99%
“…7,24 Some authors have suggested that cerebrovascular pressure reactivity could be derived from the characteristic pulse waveform from ABP, 26,27 although this has never been demonstrated to work in clinical practice. Perhaps changes in ABP are too fast (a fraction of a second) to mobilize an active vasoregulatory response.…”
mentioning
confidence: 99%
“…Decreases in ABP were observed at the beginning of plateau waves [37], and A waves [38]. Moreover, system analysis [39] suggested that a change in the transfer function that relates ABP to ICP may precede elevations. Several other investigators have also attempted to make predictions using wavelet decomposition of the ICP signal [40][41][42].…”
Section: Predicting Intracranial Hypertensionmentioning
confidence: 99%